Association between living environmental quality and risk of arthritis in middle-aged and older adults: a national study in China - Ri Liu; Yuefei Zhou; Yang Liu; Run Guo; Lishu Gao (Frontiers Media S.A., 2023)
BackgroundThe association between combined environmental factors and the risk of arthritis is still scarcely studied. The present study performed cross-sectional and cohort studies to explore the association between risk score of living environment quality and the risk of arthritis in middle-aged and older adults in China.MethodsThe study was based on China Health and Retirement Longitudinal Study (CHARLS), and it recruited 17,218 participants in the cross-sectional study and 11,242 participants in the seven-year follow-up study. The living environment quality was measured by household fuel types, household water sources, room temperature, residence types, and ambient concentration of PM2.5. Logistic regression and Cox proportional hazard regression models were utilized to examine the association between the living environment quality and the risk of arthritis. Competing risk models and stratified analyses were applied to further verify our results.ResultsCompared with individuals in the suitable environment group, people who lived in moderate (OR:1.28, 95%CI: 1.14-1.43) and unfavorable environments (OR:1.49, 95%CI:1.31-1.70) showed higher risks of arthritis when considering the multiple living environmental factors (P for trend <0.001) in the cross-sectional analysis. In the follow-up study, similar results (P for trend = 0.021), moderate environment group (HR:1.26, 95%CI:1.01-1.56) and unfavorable environment group (HR: 1.36, 95%CI: 1.07-1.74), were founded.ConclusionInferior living environment might promote the development of arthritis. It is necessary for the public, especially old people, to improve the living environment, which may be the key to the primary prevention of arthritis.